Multi-frequency long-term observations of her X-1 — The 35-d cycle - Shakura, N.; Kolesnikov, D.; Postnov, K.; Volkov, I.; Bikmaev, I.; Irsmambetova, T.; Staubert, R.; Wilms, Jörn; Irtuganov, E.; Shurygin, P.; Golysheva, P.; Shugarov, S.; et al. (Proceedings of Science, 2019)
In this work are presented the results of modelling of 35d superorbital changes of B and V lightcurves and X-ray flux of HZ Her/Her X-1. The model implemented in the new code written in C programming language, with module for parameter optimisation written in Python. The model includes a tilted precessing and warped accretion disc around a freely precessing neutron star. The disc is warped near its inner edge due to interaction with the rotating neutron star magnetosphere. The magnetic torque depends on the precessional phase of the neutron star. The X-ray emission flux from the neutron star also depends on the free precession phase which modulates the X-ray illumination of the optical star atmosphere and the intensity of gas streams. We demonstrate that this model is able to well reproduce both optical observations of HZ Her and the behaviour of the 35-day X-ray cycle.
CRIS-Team Scopus Importer:2024-12-16